2017
DOI: 10.1038/s41598-017-01394-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of a metabolic marker of infant brain function

Abstract: While near-infrared spectroscopy (NIRS) haemodynamic measures have proven to be vastly useful in investigating human brain development, the haemodynamic response function (HRF) in infants is not yet fully understood. NIRS measurements of the oxidation state of mitochondrial enzyme cytochrome-c-oxidase (oxCCO) have the potential to yield key information about cellular oxygen utilisation and therefore energy metabolism. We used a broadband NIRS system to measure changes in oxCCO, in addition to haemodynamic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…New developments in fNIRS technology will further allow us to monitor both hemodynamic and metabolic responses during newborn functional activation, with broadband instruments able to measure metabolic marker, cytochrome-c-oxidase (Bale et al, 2014 ). This metabolic marker has shown to have increased brain specificity (Kolyva et al, 2014 ; de Roever et al, 2017 ), enabling us to investigate hemodynamic metabolic coupling during neuronal activity (Bale et al, 2016 ; Siddiqui et al, 2017 ). Finally, developments in analysis techniques, such as short-separation techniques to remove scalp effects (Gagnon et al, 2011 ) enable improved data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…New developments in fNIRS technology will further allow us to monitor both hemodynamic and metabolic responses during newborn functional activation, with broadband instruments able to measure metabolic marker, cytochrome-c-oxidase (Bale et al, 2014 ). This metabolic marker has shown to have increased brain specificity (Kolyva et al, 2014 ; de Roever et al, 2017 ), enabling us to investigate hemodynamic metabolic coupling during neuronal activity (Bale et al, 2016 ; Siddiqui et al, 2017 ). Finally, developments in analysis techniques, such as short-separation techniques to remove scalp effects (Gagnon et al, 2011 ) enable improved data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was carried out in MATLAB (Mathworks, USA). A detailed description of the data analysis pipeline is described elsewhere [11]. Valid experimental trials were determined using looking time.…”
Section: Methodsmentioning
confidence: 99%
“…Fibreless systems are also likely to play an increasingly important role in neurodevelopment studies given the additional flexibility they provide for imaging brain function in naturalistic environments, especially for typically and atypically developing young infants and toddlers. Recent studies have demonstrated the first measurement of oxCCO changes during functional activation in the infant brain using a single source detector system [12], and further work is already underway to deliver spatially resolved measures of oxCCO to investigate links between mitochondrial and metabolic dysfunction in infants at high risk of autism [13,14].…”
Section: Discussionmentioning
confidence: 99%